Dexmedetomidine protects SH‐SY5Y cells against MPP+‐induced declining of mitochondrial membrane potential and cell cycle deficits. (20th May 2021) - Chen, Yaohua; Chen, Cheng; Song, Dan; Liu, Tingting; Cheng, Oumei
Abstract: Dexmedetomidine (Dex), an adrenergic α2 receptor agonist, is commonly used in deep‐brain stimulation surgery for Parkinson's disease (PD). However, there is evidence that the use of anaesthetics may accelerate the progression of neurodegenerative diseases. The effect of Dex on PD remains unclear. Here, we cultured the all‐trans‐retinoicacid (ATRA) differentiated SH‐SY5Y cells in vitro and then treated with MPP + (1.5mM) with or without Dex (10nM) or Dex combined with Atipamezole (Ati, 100nM, adrenergic α2 receptor inhibitor). The ratio of apoptotic cells, mitochondrial membrane potential (Δψm), reactive oxygen species (ROS), cell cycle and apoptotic markers (Cleaved caspase‐3, 9) were analysed by flow cytometry and immunofluorescence. We found that the levels of apoptotic ratio and cleaved caspase‐3, 9 increased, ROS accumulated, and mitochondrial membrane potential decreased after MPP+treatment, while these changes were partially reversed by Dex. Dex also prevented MPP + induced cell arrest by increasing G1 phase cells, decreasing S phase cells, and decreasing the expression of cyclinD1 and Cdk4. Moreover the effects of Dex were partially reversed by Ati. These findings reveal that Dex attenuated MPP + ‐induced apoptosis of SH‐SY5Y cells by preventing the loss of Δψm, reducing ROS, and regulating the cell cycle. Our findings indicated that Dex is more likely to be a potential drug for the treatment of PD. Abstract : Dex prevented the decrease of Δψ and the accumulation of ROS in MPP + ‐induced SH‐SY5Ycells by activating α2 adrenergic receptors. Moreover, the reduction of oxidative stress inhibited the expression of cyclinD1 and Cdk4，suppressed the activation of neuronal cell cycle and reduced cell apoptosis.